SUSTAINABLE DEVELOPMENT OF THE ORGANIZATION BASED ON LIFE CYCLE OF THE OPPORTUNITY - Królas, Paweł (Organizacja i Kierowanie, 2023)
Changes taking place in individual sectors of the economy require organizations to adapt their operational and systemic activities to the requirements of the main players in the sector. When an organization will not face the strategic clients’ requirements the existence of the supplier organization could be at risk. The main aim of the work was to present the changes taking place in a selected sector of the economy. The paper presents the results of assessment carried out in a consulting company dealing with pro-quality systems. Using the example of a selected customer from the automotive industry, the life cycle of the opportunity was presented based on the implemented systems as well as the chosen action of Quality Management Systems (QMS) applied in the organization. Thanks to this, the company from the automotive industry was able to meet the requirements of a strategic client.